Pemanfaatan Smartphone Bagi Petani Sebagai Alat Pengukur pH Tanah di Desa Tanggalrejo Mojoagung Jombang - Nasirudin, Mohamad; Zulfikar, Zulfikar; Muhibuddin, Anton; Ashar, Salim; Indana, Izzatul; Zakaria, Ari Viqri; Aminah, Siti; Mei Sintia, Khusnul (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Technology in agriculture is something that cannot be separated from its application in the agricultural sector. The use of smartphones in soil pH measuring devices makes the measurement process faster, easier and more affordable. This research aims to develop a simple and affordable soil pH measuring tool for use by farmers in Tanggalrejo Village, Mojoagung, Jombang. The method approach taken for community service in Tanggalrejo Village is to use the Participatory Action Research (PAR) method. One of them is by implementing training methods and approaches from local farmers so that indirectly farmers in Tanggalrejo Village can capture the material well. This tool is named